Design and synthesis of highly oxygenated furo[3, 2‐c]pyran‐4‐ones and furo[3, 2‐c]chromen‐4‐ones scaffold as anticancer and antimicrobial agents. (8th October 2021) - Rani, Suman; Kumar, Devinder; Kamra, Nisha; Thakral, Sumit; Singh, Ajeet; Sangwan, Payare L.; Singh, Shashank K.
Abstract: Synthesis of a number of highly oxygenated furo[3, 2‐c]pyran/chromen‐4‐one has been accomplished by one‐pot reaction from easily available dehydroacetic acid/3‐acetyl‐4‐hydroxycoumarin or their chalcones and α‐bromoketones. All the synthesized molecules were characterized utilizing various spectroscopic techniques and screened for anticancer activity (in vitro) against three colon (HCT‐116, SW‐620, HT‐24), lung (A‐549), prostate‐(PC‐3), breast (MCF‐7) cell lines. Compounds 5a, 9d, 9f showed good activity against breast MCF‐7 cancer cell line having IC50 values 6.9, 2.8, 5.3 μM, respectively. Of these compounds, 9d showed better activity against prostate PC‐3 cell line with IC50 value 3.8 μM. The synthesized compounds were also studied for antibacterial activity (in vitro) using different strains of bacteria ( Bacillus subtilis and Staphylococcus aureus – Gram‐positive and Escherichia coli, Pseudomonas aeruginosa – Gram negative) as well as fungal strains ( Aspergillus niger and Candida albicans ) using Norfloxacin and Fluconazole as antibacterial and antifungal standard drugs, respectively. The antimicrobial screening study showed that compound 9f exhibited promising activity against S. aureus and B. subtilis, while 5h showed excellent and 5i and 9b showed better activity against E. coli . Compounds 5d and 5e showed promising activity against P. aeruginosa . The compounds 5c –5e displayed excellent activity against C. albicans and A. niger than Fluconazole. Abstract : Synthesis of highly oxygenated 4H‐furo[3, 2‐c]pyran/chromen‐4‐ones have been accomplished and evaluated for in vitro anticancer activity against six different cell lines and four bacterial strains and two fungal strains. Norfloxacin and Fluconazole are used as reference drugs for antibacterial and antifungal activity.